Amount of Fibrin in Different Organs after Intravenous, Intraportal and Intraaortal Injection of Thrombin in the Rat - Busch, Christer; Saldeen, Tom (Thrombosis and Haemostasis, 1973)
The effect of intravenous, intraaortal and intraportal injection of thrombin on the distribution of intra vascular fibrin in various organs was determined by a quantitative method in the rat. It was found that the major part of the fibrin was trapped in the lungs irrespective of the route of administration of the thrombin.These results suggest that in thrombin induced intravascular coagulation most of the coagulation occurs on the venous side of the circulation.This mechanism may be an explanation for the fact that certain organs more often contain intravascular fibrin than others at autopsy.